Internal control and audit of public sector organizations: Risk assessment - Safina, Albina R. (2018)
A noticeable role in economic life of any society is played by the state. Now practically all countries of the world assume existence of public sector of economy. The Russian Federation is also among such countries. The most important direction of increase in efficiency of modern public administration is development risk - the focused internal control and audit on the basis of application of achievements of science and technology. In this article questions of assessment of risks when carrying out internal control and audit of the organizations of public sector which are insufficiently opened in literature now are considered and demand studying of the international experience and the annex to practical situations. For practical realization of processes of internal control and audit the need for highly effective approaches to assessment of risks more and more increases. In work we carried out application of the standardized approaches to assessment of the risks acquired in the sphere of independent audit, internal control and internal audit first of all for the commercial sector in processes of internal control and audit of the organizations relating to public sector. For evaluating risks in public sector areas of risks of essential distortion for this sector were allocated, the approximate list of control questions is developed for testing by internal controllers and auditors of risks of essential distortion of information in the organizations of public sector, the method of calculation of components of auditor risk is given.